ENERGY EFFICIENCY OF ELECTRIC HEATING OF REACTORS IN THE MANUFACTURE OF VARNISHES AND PAINTS - Tovajniansky L.L.; Ved V.E.; Gurina G.I. (Problems of the Regional Energetics, 2014)
The drawbacks of the traditional design of the heaters, which make known imperfections in manufacturing processes, realized with the use of electric heating. This determines the need for a radically new design of the heating devices. Created by high-temperature ceramics, characterized by abnormally high thermal stability and clarified the parameters that allow a certain degree change its thermal conductivity. On this basis the contact type ceramic heaters that provide thermal flow direction using different materials in the body of the heater - of high thermal conductivity, the surface facing the heat transfer and low which differs opposite sides of the heater are designed to eliminate the dissipation of heat into the surrounding space. This made it possible to equip the modern production paint industry energy efficient heating equipment with explosion and fire heating system reactors.